High-level radioactive waste repository: How Geology combined with societal principles can lead to public acceptance—the German experiment - Schafmeister, Maria-Theresia (Comptes Rendus. Géoscience)
Using nuclear power for civil energy generation was a promising idea in the second half of the 20th century. Compared to fossil fuels, nuclear power results in almost no $CO_{2}$ bearing emissions, which are known to have triggered and enhanced the global climate change. However, nuclear power bears other risks, e.g. environmental and health damage caused by radiation, unwanted release of nuclides being transported by water, accidents of nuclear power plants, and not to mention the possibility of non-intended military use. In any case, generating power from nuclear fission will always produce radiating waste, albeit in small amounts. Due to its longevity, this waste is a significant challenge for scientists, politicians and for the international social community to find a repository, which can be considered safe for millions of years and is accepted by the public. As the general consensus is that the rocks of earth crust’s are the best option for a controlled storage, scientists including geologists, geophysicists and hydrogeologists are looking worldwide for safe underground repository sites. Given different political preconditions, the nations, especially in the European Union, have developed different strategies. The following article intends to describe the current strategy in Germany, which is based on a specific “Act on the search for and selection of a site for a final repository for highly radioactive waste” (in short: Site Selection Act) and attempts to learn from mistakes in the seventies. It is our strong conviction that fundamental geological aspects are as important as essential societal principles in order to gain maximum public acceptance.